2009
DOI: 10.3109/17453670903413111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dynamic compressive loading and its combination with a growth factor on the chondrocytic phenotype of 3-dimensional scaffold-embedded chondrocytes

Abstract: Background and purpose Three-dimensionally (3D-) embedded chondrocytes have been suggested to maintain the chondrocytic phenotype. Furthermore, mechanical stress and growth factors have been found to be capable of enhancing cell proliferation and ECM synthesis. We investigated the effect of mechanical loading and growth factors on reactivation of the 3D-embedded chondrocytes.Methods Freshly isolated chondrocytes from rat articular cartilage were grown in monolayer cultures and then in collagen gel. Real-time R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Elder et al [63] demonstrated that low amplitude cyclic compression at 0.33 Hz promoted GAG synthesis of mesenchymal cells from chick limb bud embedded in agarose gel. Furthermore, we also found that cyclic compressive loading of 5% amplitude in cycles of 3s stimulated cartilage-specific ECM synthesis by chondrocytes embedded in type I collagen gel [76].…”
Section: Dynamic Compressive Loadsupporting
confidence: 56%
“…Elder et al [63] demonstrated that low amplitude cyclic compression at 0.33 Hz promoted GAG synthesis of mesenchymal cells from chick limb bud embedded in agarose gel. Furthermore, we also found that cyclic compressive loading of 5% amplitude in cycles of 3s stimulated cartilage-specific ECM synthesis by chondrocytes embedded in type I collagen gel [76].…”
Section: Dynamic Compressive Loadsupporting
confidence: 56%
“…The chondrogenic differentiation of mesenchymal stem cells from bone marrow, adipose tissue, and umbilical cord has been explored 41112. One of the major issues in chondrocyte expansion is the quality of the chondrocytes grown in vitro , mainly its ability to retain its phenotype in culture, if hyaline cartilage regeneration is to be achieved 41113. There is a good source of autogenous chondrocyte in the iliac apophyseal growth plate in children, which can be potentially used for treating growth plate abnormality and articular cartilage defects 14.…”
Section: Discussionmentioning
confidence: 99%
“…But the difficulty of single-layer chondrocyte culture is that the cells undergo de-differentiation (they lose their specific characteristics), which results in failure to synthesize hyaline cartilage thereby losing therapeutic efficacy. To address this methodological problem, an attempt was made to culture these cells in 3D matrices, which did result in the secretion of growth factors, but exposed the chondrocytes to mechanical stress [16]. A solution for this, put forward by Maher et al [17], consisted in the incorporation of chondrocytes to biomaterials such as nanofiber hydrogels.…”
Section: Cell Therapymentioning
confidence: 99%